CONTENT VALIDITY AND RELIABILITY OF A STUDENT PERFORMANCE ASSESSMENT INSTRUMENT IN COLLABORATIVE PROBLEM SOLVING-BASED MATHEMATICS LEARNING - Isnurani Isnurani; Wardani Rahayu; Iva Sarifah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aimed to examine the content validity and internal reliability of a student performance assessment instrument for mathematics learning based on Collaborative Problem Solving (CPS). The participants of this study were 45 students from a private high school in South Tangerang, Banten. The instrument is a self-assessment questionnaire with 32 statements based on four dimensions of Collaborative Problem Solving (CPS), namely cognitive, social, emotional, and metacognitive. Content validity in this study uses Aiken's V index test, while internal reliability is analyzed using Cronbach's Alpha. The results showed that most items had fairly good validity with an Aiken's V value ≥ 0.60, but there were 11 items with values below 0.60 that needed improvement. Meanwhile, the reliability value of the instrument was very high with a Cronbach's Alpha value above 0.90 for each dimension and 0.986 overall. These findings confirm that the instrument is suitable for use as a comprehensive measurement tool in supporting mathematics learning transformation based on collaborative problem solving.